The Application of DVDMS as a Sensitizing Agent for Sono-/Photo-Therapy - Mai, Bingjie; Wang, Xiaobing; Liu, Quanhong; Zhang, Kun; Wang, Pan (Frontiers in Pharmacology, 2020)
Both photodynamic therapy (PDT) and sonodynamic therapy (SDT) are fast growing activated therapies by using light or ultrasound to initiate catalytic reaction of sensitizing agents, showing great potentials in clinics because of high safety and non-invasiveness. Sensitizers are critical components in PDT and SDT. Sinoporphyrin sodium (DVDMS) is a newly identified sensitizer derived from Photofrin that has been approved by FDA. This review is based on previous articles that explore the applications of DVDMS mediated photodynamic/sonodynamic cancer therapy and antimicrobial chemotherapy. Researchers utilize different cell models, distinct treatment protocols to explore the enhanced therapeutic response of neoplastic lesion. Moreover, by designing a series of nanoparticles for loading DVDMS to improve the cellular uptake and anti-tumor efficacy of PDT/SDT, which integrates diagnostics into therapeutics for precision medical applications. During the sono/photo-activated process, the balance between oxidation and anti-oxidation, numerous signal transduction and cell death pathways are also involved. In addition, DVDMS mediated photodynamic antimicrobial chemotherapy (PACT) can effectively suppress bacteria and multidrug-resistant-bacteria proliferation, promote the healing of wounds in burn infection. In brief, these efficient preclinical studies indicate a good promise for DVDMS application in the activated sono-/phototherapy.